2021
DOI: 10.1021/acscatal.1c01991
|View full text |Cite
|
Sign up to set email alerts
|

Dictating Catalytic Preference and Activity of a Nanoparticle by Modulating Its Multivalent Engagement

Abstract: Incorporating adaptive and dynamic behavior in a catalytic system is the foremost prerequisite to gain nature-like complex functionality in a synthetic chemical network. Herein, we report a self-assembled modular catalytic system based on the multivalent interaction between a cationic gold nanoparticle surface and nucleotides. It is shown that the catalytic preference and activity of the nanoparticle can be directed in a controllable manner toward either hydrazone formation or a proton transfer reaction only b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 60 publications
0
29
0
Order By: Relevance
“…[33][34][35] Recently, we have shown that the catalytic ability of a cetyltrimethylammonium bromide (CTAB)-functionalized cationic gold nanoparticle (GNP) can be up-and downregulated by exploiting multivalent interactions between GNPs and adenosine-based nucleotides. 35 The alteration of the local surface pH of the GNPs due to the assembly of these differently charged nucleotides was the key reason for this modulatory catalytic behavior. In the present work, we have also synthesized and characterized CTAB-capped GNPs with a diameter of 20 AE 3 nm and a positive surface zeta potential of 85 AE 5 mV (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…[33][34][35] Recently, we have shown that the catalytic ability of a cetyltrimethylammonium bromide (CTAB)-functionalized cationic gold nanoparticle (GNP) can be up-and downregulated by exploiting multivalent interactions between GNPs and adenosine-based nucleotides. 35 The alteration of the local surface pH of the GNPs due to the assembly of these differently charged nucleotides was the key reason for this modulatory catalytic behavior. In the present work, we have also synthesized and characterized CTAB-capped GNPs with a diameter of 20 AE 3 nm and a positive surface zeta potential of 85 AE 5 mV (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Notably, physical properties, such as pH and polarity, in the microenvironment of the micellar interface are different than those in bulk solution; and this property is also preserved in surfactant-layer-anchored nanoparticle surfaces. 33–35 Recently, we have shown that the catalytic ability of a cetyltrimethylammonium bromide (CTAB)-functionalized cationic gold nanoparticle (GNP) can be up- and downregulated by exploiting multivalent interactions between GNPs and adenosine-based nucleotides. 35 The alteration of the local surface pH of the GNPs due to the assembly of these differently charged nucleotides was the key reason for this modulatory catalytic behavior.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[11] However, it has been established that mixed-valence states in nanomaterials coordinating environment exhibit extraordinarily high catalytic efficiencies due to the synergism among oxidation states. [12,13] Overlooking the tunability of the oxidation states of single atoms in SACs can, therefore, preclude the catalytic potential of these materials. Although, a few studies have been conducted on the effects of oxidation states of metal centers in precursors, they were only limited to the geometric and structure-dependent properties of the catalysts instead of the quantum dynamics of their oxidation states.…”
Section: Introductionmentioning
confidence: 99%